FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN PUBLIK SEKTOR MANUFAKTUR - YULIUS KURNIA SUSANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2009)
The purpose of the study is to investigate over the acceptance of going concern audit opinion which can be performed by observing company’s financial condition, current ratio, quick ratio, cash flow from operations, return on assets, debt to equity, long term debt to total assets, debt to total assets, audit quality, prior audit opinion, debt default and opinion shopping. Samples are obtained by sampling pur-posive method. Data for this study comprises of the information from the financial statement of the public manufacturing companies in Indonesia over the four year period 2005 until 2008, and the result obtained 260 observations. The logistic regression used to examine the factors that are predicted to affect the probability of acceptance of going concern audit opinion. The result of this research is that com-pany’s financial condition (Revised Altman Model), return on assets, debt to total assets and prior audit opinion are significantly affect the probability of acceptance of going concern audit opinion. On the other hand, current ratio, quick ratio, cash flow from operations, debt to equity, long term debt to total assets, audit quality, debt default and opinion shopping, do not so.